2021
DOI: 10.1111/1911-3846.12684
|View full text |Cite
|
Sign up to set email alerts
|

Do Stronger Wise‐Thinking Dispositions Facilitate Auditors' Objective Evaluation of Evidence When Assessing and Addressing Fraud Risk?*

Abstract: The objective evaluation of evidence is imperative for audit effectiveness and the proper exercise of professional skepticism. However, numerous studies suggest that auditors fail to evaluate evidence objectively when assessing or addressing the risk of material misstatement due to fraud. We develop theory to predict that auditors do evaluate evidence objectively but only when they have stronger wise‐thinking dispositions (WTDs), a construct that is new to the audit literature. We define WTDs as the tendency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 101 publications
(151 reference statements)
0
2
0
Order By: Relevance
“…P16, P17 and P20 provided more clarity on integrity to cover good governance, business ethics and morality, with some participants also sharing their previous employment experiences. The CFO’s decision-making process and actions are consistently associated with integrity and business ethics, according to Brewster et al (2021), Fleischman et al (2022) and Sidaway et al (2023). CFOs are uniquely placed within organizations to lead corporate governance, which establishes a set of rules and practices that govern how a company operates and aligns the interests of all stakeholders.…”
Section: Resultsmentioning
confidence: 99%
“…P16, P17 and P20 provided more clarity on integrity to cover good governance, business ethics and morality, with some participants also sharing their previous employment experiences. The CFO’s decision-making process and actions are consistently associated with integrity and business ethics, according to Brewster et al (2021), Fleischman et al (2022) and Sidaway et al (2023). CFOs are uniquely placed within organizations to lead corporate governance, which establishes a set of rules and practices that govern how a company operates and aligns the interests of all stakeholders.…”
Section: Resultsmentioning
confidence: 99%
“…Zamboni, Y. et al investigate whether an increase in the audit risk of local government activities in Brazil affects rent extraction, with estimates showing that an increase in the audit risk of 20 points corresponds to a decrease of 10 percentage points in the proportion of resources involved in procurement corruption [20]. Brewster, B. E. et al reported an experiment that found large differences in the strength of auditors' propensity to think wisely (wtd) and demonstrated that the audit judgment quality effect of stronger wtd was reproducible [21]. This paper proposes the internal audit performance evaluation system of colleges and universities based on the balanced scorecard and constructs the corresponding strategy map and evaluation indexes.…”
Section: Introductionmentioning
confidence: 99%
“…Although the audit literature examines how auditors evaluate behavioural attributes, such as competence, of internal and other external auditors (e.g., Brown, 1983; Han et al, 2011; Harding & Trotman, 2009; Kennedy & Peecher, 1997; Margheim, 1986; Schneider, 1984; Tan & Jamal, 2001; Tan & Jamal, 2006), considerably less research has examined how auditors test such characteristics of client management. Research that has examined characteristics of client management (e.g., Brewster, 2016; Brewster et al, 2021; Hirst, 1994) has focused on the evaluation of evidence made available to auditors, not the steps auditors take to actively generate such evidence. Better understanding these steps can enable development of decision aids to assist in the crucial evidence gathering process.…”
Section: Introductionmentioning
confidence: 99%